Update on Cancer-Associated Venous Thromboembolism in Children - Kasteler, Rahel; Albisetti, Manuela; Bosch, Alessandra (Hämostaseologie, 2024)
Children with cancer have an increased risk for venous thromboembolic events (VTEs) compared to the healthy pediatric population. VTE rates in children with cancer vary among cancer types. Other VTE risk factors include central venous catheters and cancer therapies. VTE diagnosis relies on objective radiological imaging, and management to this date typically involves anticoagulant therapy. Low-molecular-weight heparins (LMWHs) are the most common choice. Evidence for primary VTE prevention is conflicting, and antithrombin replacement, LMWH, or apixaban have been studied. Recently, direct oral anticoagulants such as rivaroxaban or dabigatran were investigated for VTE treatment, showing promise in efficacy and safety. However, bleeding risks in this population need careful consideration, especially periprocedurally or with treatment-related thrombocytopenia. Prediction tools for VTE require adaptation for pediatric cancer patients. Progress in understanding and managing VTE in children with cancer is significant, with ongoing trials and real-world data contributing to improved strategies.
Keywords: venous thromboembolism; childhood cancer; anticoagulants; primary prevention